Implementasi Nikah Muda dalam Keharmonisan Rumah Tangga - Rizqi K I, A Aprizal (UNES Law Review, 2024)
Young marriage is one of the marriage activities carried out by underage couples or when they are still students. Young marriage has been widely practiced by Indonesian people who still do not understand harmony in the household. The purpose of this writing is to analyze the implementation of young marriage in household harmony. The method used in the research uses a qualitative type. The results obtained by harmony in a household can be seen from the achievement of good communication, relationships based on love, peace and happiness. Based on a literature study conducted, some households have not been able to achieve a sense of harmony in the household due to several factors, one of which is the age of the husband or wife. This could be caused by the psychological feelings of the bride and groom who are not yet stable or immature, so that it will be more dominant in triggering conflict in the household. Apart from that, conflicts within the household can also arise due to economic problems.